2010
DOI: 10.1007/s11258-010-9833-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in flood frequency increase exotic and native species richness of understorey vegetation in a temperate floodplain eucalypt forest

Abstract: The delivery of environmental flows for biodiversity benefits within regulated river systems can potentially contribute to exotic weed spread. This study explores whether exotic plants of a floodplain forest in Victoria, Australia, are characterised by specific functional groups and associated plant traits linked to altering hydrological conditions over time. Permanently marked 20 9 20 m 2 plots from five wetland sites in Eucalyptus camaldulensis floodplain forest were sampled twice, first in the early 1990s (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…These experimental results support conclusions from surveys and modelling studies that floods provide an effective method to control exotic annuals on river floodplains (Stokes, Ward & Colloff ; Catford et al . ), in the short term at least.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These experimental results support conclusions from surveys and modelling studies that floods provide an effective method to control exotic annuals on river floodplains (Stokes, Ward & Colloff ; Catford et al . ), in the short term at least.…”
Section: Discussionsupporting
confidence: 84%
“…This ‘terrestrialization’ hypothesis (Catford et al . ) posits that annual, terrestrial exotic plants have invaded floodplains following a reduction in the frequency, magnitude and duration of floods (Stokes, Ward & Colloff ; Catford et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sites of low flood frequency are more sensitive to future exotic weed invasion and will require targeted management effort. Flow restoration is predicted to benefit propagule dispersal of species adopting dual regeneration strategies, which are predominantly native species in this system (Stokes et al 2010). The invasion by alien plant species is a major challenge to the conservation and management of riparian areas which can alter ecosystem structure and function in undesirable ways (Hood and Naiman 2000;Stohlgren et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that reduced flooding as a result of river regulation and water extraction has favoured exotic species (Stokes et al 2010, Catford et al 2011. However, other disturbance factors, including agricultural activities, urban development, recreational activities and logging, have also promoted weed invasion.…”
Section: Weed Invasionmentioning
confidence: 99%